The Role of User Competence in the Implementation of Accounting Information Systems and Its Impact on the Quality of Accounting Information - Fadjar, Achmad; Riyanto, Irfansyah; Septiana, Widia (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research is a case study at PT Bersama Zatta Jaya because incorrect or incomplete information is still found from the accounting information system used by the company. The success of the implementation of information systems can be influenced by several factors including the competence of human resources. Information systems specialists who have the competence, skills and experience to manage the technical and behavioral aspects of information systems are the driving force for the success of high-quality information systems. This study aims to determine the effect of competence on the successful implementation of accounting information systems and their impact on the quality of accounting information.The objects in this study are competence, accounting information systems and the quality of accounting information at PT Bersama Zatta Jaya. Data collection techniques by distributing questionnaires with the number of samples in this study as many as 50 respondents using path analysis techniques with SPSS tools.The results of the study show that competence affects the success of the implementation of accounting information systems and accounting information systems affect the quality of accounting information